KEANEKARAGAMAN HAYATI KAMPUS IPB BARANANGSIANG - Harnios Arief (Department of Forest Resources Conservation and Ecotourism - IPB University, 2014)
IPB campus spread at some locations, one of the location is IPB Baranangsiang campus. Along with development of Bogor city, especially around the Bogor Botanical Garden and IPB Baranangsiang campus, so it is needed doing study in order to get description about condition of biodiversity at IPB Baranangsiang campus. The purpose of this study is to show information about the condition of campus biodiversity, both the diversity of flora and fauna. The data about flora was conducted by field observation method by census and the data about fauna was conducted by interview and field direct observation, either directly or by voice encounter and the trail left as dirt, nest, scratch marks, footprints, and others. The result showed that there were 34 species of flora found and two species were protected. Found fauna was 30 species of birds, four species of amphibian, 17 species pf reptile, seven species of mammals and there was one species was protected. ‘Taman Koleksi’ and back door gate/border river were area whis had richness of fauna higher than other area.Keywords: Biodiversity, Fauna, Flora, IPB Baranangsiang Campus